Parental Background Variables and the Career Choice of Secondary School Students in Uyo Local Government Area, Nigeria - Udoh, Nsisong Anthony; Sanni, Kudirat Bimbo (Mediterranean Journal of Social Sciences, 2012)
The study investigated the influence of parental background variables (Parentsâ€™ attitudes towards occupations,Parentsâ€™ levels of formal education, and Parentsâ€™ occupation) on the career choice of secondary school student in Uyo LocalGovernment Area. Three hypotheses were raised to guide the study. This ex-post-facto survey employed the simple randomsampling technique in obtaining data from a sample of 200 SS3 students from 11 public secondary schools in Uyo LocalGovernment Area using the â€œParental Variables and Career Choice Questionnaireâ€ (PVCQ) designed by the researchers. Thehypotheses were subsequently tested using chi square at pâ‰¤.05 level of significance. Data analyses revealed that parentsâ€™attitudes towards occupations, parentsâ€™ level of formal education, and parentsâ€™ occupation exert influence on the career choice ofsecondary school students in Uyo Local Government Area. It was recommended that parents should desist from pressuringtheir children into taking up careers they do not possess the requisite abilities and that government should train and employmore career counsellors to assist these students in their career choice and preparation through the implementation of acomprehensive programme of career education.